Analisis Historis terhadap Corak Kesenian Islam Nusantara - Nurrohim Nurrohim; Fitri Sari Setyorini (Millati: Journal of Islamic Studies and Humanities, 2018)
The history of Islamic development in Indonesia has different characteristics compared to other Islamic regions such as Turkey, India, Egypt, Syria, and Morocco. The journey of Islam in Indonesia brings different colors and patterns that distinguish it from other Islamic regions. This happens because Islam is spreaded in the archipelago peacefully and in a gradual long time, unlike the other Islamic regions islamization which is not infrequently through the power of the armed forces. This article will explain the results of Islamic interaction with society who previously embraced Hinduism, Buddhism and animist beliefs dynamism in the form of Islamic Nusantara arts. The analytical method used in this paper is a combination of theories of acculturation and assimilation of Nusantara culture and Islamic culture. The combination of Nusantara culture and Islamic culture produces an Islamic art with the uniqueness of Nusantara without eliminating the elements of the old culture. The form of pre-Islamic Nusantara cultural heritage with the Islamic culture can be found in the architecture of mosques, Arabic Malay script, literary arts, painting and sculpture.